Sexual dimorphism in the migratory dynamics of a land-locked population of brown trout (Salmo trutta) in central Sweden - Vigren, Carl (2018)
In this study I use a 56 years long dataset to study the migratory behaviours of a land-locked population of Brown trout (Salmo trutta) in the river Dammån, positioned in central Sweden. I found that there was a mean female-to-male sex ratio in the spawning-run of approximately 2.31 with an average 50% run date on the 29th of July.